👤

write the standard form of the c(4,5) r= 2 and c(-3,2) r= √5​

Sagot :

[tex] \huge{ \color{lightgreen}{ \mathcal{Answer:}}}[/tex]

------------------------------------------------------------------

Write the standard form of the c(4,5) r= 2 and c(-3,2) r= √5.

------------------------------------------------------------------

Standard Form of C(4,5) r=2

Formula:

[tex] \sf(x - h)^{2} + (y - k) ^{2} = {r}^{2} [/tex]

Given:

[tex] \sf \large \:h = 4[/tex]

[tex] \sf \large \: k = 5[/tex]

[tex] \sf \large \: r = 2[/tex]

Solution:

[tex] \sf(x - h)^{2} + (y - k)^{2} = {r}^{2} [/tex]

[tex] \sf(x - 4)^{2} + (y - 5) ^{2} = {2}^{2} [/tex]

[tex]\large{ \red{ \boxed{ \boxed{ \sf{(x - 4)^{2} + (x - 5) ^{2} = 4}}}}}[/tex]

------------------------------------------------------------------

Standard Form of C(-3,2) r=5

Formula:

Same as The First Standard Form.

Given:

[tex] \sf \large \: h = - 3[/tex]

[tex] \sf \large \: k = 2[/tex]

[tex] \sf \large \: r = \sqrt{5} [/tex]

Solution:

[tex] \sf(x - h)^{2} + (y - k)^{2} = {r}^{2} [/tex]

[tex] \sf(x + 3)^{2} - (y - 2)^{2} = \sqrt{ {5}^{2} } [/tex]

[tex] \large\red{ \boxed{ \boxed{ \sf{(x + 3)^{2} + (y - {2})^{2} = 5}}}}[/tex]

------------------------------------------------------------------

#CarryOnLearning